Antioxidant Activity And Total Phenolic Content Of Date Palms Syrup (Phoenix Dactylifera L) - Yetri Elisya; Harpolia Cartika; Anindita Rizkiana (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2017)
Palm date fruits (Phoenix dactylifera L) have been used for medical treatment, one of the medical purpose as antioxidant, which is the coumpound for free radical scavenging. In this study used palm juice makes with non sentrifuged method by grounds 200 grams of palm fruit with 20 ml of aquadest and store in room temperature. For date palm syrup used in this study were from certain brand distributed on the market. Antioxidant activity was testing by using DPPH method and determined by spectrophotometry Uv-Vis in wavelength 517nm, and Total Phenolic Content was testing by Folin Ciocalteu method and determined by spectrophotometry Uv-Vis in wavelength 774nm.11 sample of date palm syrup was sampling by purposive sampling methods and then got 2 sample to tested. Date Palm Juice were made by Non Cetrifuged methods. All sample were tested antioxidant activity using DPPH and Total Phenolic Content using Folin Ciocalteu. This study obtained that best operating time for all sample in antioxidant activity is 30 minutes with the highest point is Date Palm Juice 91,54%, Sample X for 86,93% and Sampel Y 89,92%. There was a linear correlation between with the result Total Phenolic Content for Date Palm Juice 9,25 mgGAE/g, Sample X 4,13 mgGAE/g and Sampel Y 4,28 mgGAE/g. Date Palm Juice and Date Palm Syrup could scavenge free radical DPPH in huge concentration and contain phenolic compound.